IITA’s genebank, cowpea diversity on farms, and farmers’ welfare in Nigeria - Kouakou, A.G.; Ogundapo, A.T.; Smale, M.; Jamora, Nelissa; Manda, J.; Abberton, Michael T. (Springer, 2022)
Background Cowpea or black-eyed pea (Vigna unguiculata L.) is one of the preferred food crops in Nigeria, as expressed in land area and production. The popularity of the crop is in part related to the successful development and adoption of improved cowpea varieties. Although the genebank of the International Institute of Tropical Agriculture (IITA) has contributed to cowpea conservation and improvement efforts by breeding programs internationally and in Nigeria, few studies have attempted to link the genebank to the management of cowpea genetic resources (CGRs) on farms. This study explores the linkage between IITA’s genebank and cowpea variety diversity on farms and other measures of farmers’ welfare in Nigeria.